Impact of cellular and medium properties on depletion-mediated red cell aggregation - Rad, Samar (2012)
The reversible red blood cell aggregation induced by polymers or proteins continues to be of biological and biophysical interest and the details regarding this process are still being explored. A depletion mechanism has been proposed for dextran-mediated RBC aggregation and its applicability to high molecular weights has been recently documented. In part of this study, the depletion layers around the cell surface for various polymer sizes (40kDa-28MDa), ionic strengths (5 and 15mM) and polymer concentrations (≤0.9g/dl) are measured by means of electrophoretic mobility. The results indicate that the impact of bulk viscosity on the red cell mobility is reduced by increasing the polymer size, and mobility values are higher than that predicted by Helmholtz-Smoluchowski equation. These results agree with the concept of polymer depletion near the cell surface and support a depletion mechanism for dextran-mediated red cell aggregation. Furthermore, the interaction energies between cells have been calculated by considering cellular and medium properties. The impact of glycocalyx thickness, volume fraction, structure and charge density as well as bulk polymer size and concentration on the cell-cell affinity are calculated. The theoretical model predicts a non-monotonic dependence of cell-cell affinity to polymer size and concentration which suggests an optimum dextran size and concentration for inducing adhesion. These results agree quantitatively with recent experimental observations. Our findings provide important new insights into polymer-RBC interactions and confirm the concept of depletion mechanism for RBC aggregation which may help in understanding how cellular properties control in-vivo RBC interactions.